Avaliação qualitativa de nascentes com diferentes coberturas do solo e conservação da vegetação em seu entorno no córrego Pimenta - Marmontel, Caio Vinicius Ferreira [UNESP]; Rodrigues, Valdemir Antonio [UNESP] (My University, 2015)
The sources lose their qualitative and quantitative capacity of water, when it is changed by human actions. The objective of this research was to evaluate qualitatively four water sources and the positive and negative impacts on their surroundings in creek Pimenta, as well as the framing of each source in CONAMA Resolution 357/05. For the physical characterization of the sources and their surroundings, they were classified as preserved, disturbed or degraded, beyond the positive and negative environmental impacts. Sampling of surface water were made in the period of one year, with ten physicochemical parameters monitored. The first source (N1) it is preserved and presents coverage of riparian forest. The source two (N2) has coverage of riparian forest and is in a state of disturbance. The source three (N3) has coverage of bamboo forest and natural forest and it is degraded. The source four (N4) has pasture cover and is in degradation. The adjust of physico-chemical parameters had the N1 within the standards for Class II, the N2 is adjusting for Class III, N3 and N4 did not show the values allowed in class II and III. The sources preserved and disturbed with riparian vegetation had all positive impacts, while degraded sources have the most negative impacts. The presence of riparian vegetation in disturbed and preserved sources auxiliary in qualitative protection of water resources compared the degraded sources.

As nascentes perdem a capacidade quantitativa e qualitativa da água, quando alteradas por ações antrópicas. O objetivo desta pesquisa foi realizar a avaliação qualitativa de quatro nascentes, visando avaliar os impactos positivos e negativos no seu entorno no córrego Pimenta, bem como o enquadramento de cada nascente na Resolução CONAMA 357/05. Para a caracterização física das nascentes e do seu entorno foram classificadas em preservada, perturbada ou degradada, além dos impactos ambientais positivos e negativos. As amostragens de águas superficiais foram efetuadas no período de um ano, com dez parâmetros físico-químicos monitorados. A nascente um (N1) está preservada e apresenta cobertura de mata ciliar. A nascente dois (N2) tem cobertura de mata ciliar e se encontra em estado de perturbação. A nascente três (N3) possui cobertura de bambuzal e floresta natural e está degradada. A nascente quatro (N4) tem cobertura de pastagem e se encontra em degradação. O enquadramento dos parâmetros físico-químicos teve a N1 dentro dos padrões para a classe II, a N2 se enquadrou para a classe III, a N3 e N4 não apresentaram valores ao permitido na classe II e III. As nascentes com vegetação ciliar preservada e perturbada apresentaram todos os impactos positivos, enquanto as nascentes degradadas apresentaram a maioria dos impactos negativos. A presença de vegetação ciliar nas nascentes preservada e perturbada auxiliou na proteção qualitativa dos recursos hídricos quando comparadas as nascentes degradadas.
Qualitative evaluation of sources with differents covers and conservation of vegetation in its surroundings on the creek Pimenta
Keywords: Environmental impacts; Source preserved; Source disturbed; Source degraded; Riparian vegetation; Impactos ambientais; Nascente preservada; Nascente perturbada; Nascente degradada; Vegetação ciliar